Acmeology development (from the 20-th years of the XX cen. to beginning of the XXI cen.): stages of development and their characteristics - Dereka Tetiana (Borys Grinchenko Kyiv Metropolitan University, 2017)
The article describes and characterizes the development of acmeology as a science. The peculiarities of acmeology development starting from the 20-th years of the 20-th century and to the beginning of the 21-st century. There are following stages of acmeology formation defined: fundamental, synergetic-technological, professional-applied, academic-scientific and creative-integrative. The peculiarities of the acmeology formation are characterized as well as the stages of development as a science that studies the patterns and phenomena of human development in the process of self-improvement, the purposeful movement to the professional and personal acme are defined. The article outlines the stages of acmeology development on the territory of Ukraine. The fundamental stage (1928 - 1950) is characterized by the definition of «acmeology» concept and its place in the system of human sciences. Synergetic-technological (1951 - 1966) stage is characterized by the definition of laws and methods of human perfection achieving. Professional-applied stage (1967 - 1984) is characterized by the professional environment studying methods development, the advanced training system development as well as specialists' achievement of professional skills. Academic-scientific stage (1985 - July 1991) is characterized by registration in the USSR State Committee of Science and Technology acmeology as a branch of science, forming of acmeology departments in higher educational institutions and foundation of the scientific and practical journal «Acmeology». The creative-integrative stage (from August 1991 to the present) is characterized by acmeology development in independent Ukraine, the study of macro- and micro-akme formation peculiarities as well as investigation of social, professional and personal acme ways of achievement. The peculiarity of this stage is the first Ukrainian organization «Ukrainian Academy of Acmeology» foundation (01.07.2006).